Victor Frankenstein - Davis, John, 1954-; McGuigan, Paul, 1963-; Landis, Max, 1985-; Radcliffe, Daniel, 1989-; McAvoy, James, 1979-; Findlay, Jessica Brown, 1989-; Scott, Andrew, 1976 October 21-; Fox, Freddie, 1989-; Dance, Charles; Armstrong, Craig, 1959-; Wagner, Fabian, 1978-; Twentieth Century-Fox Film Corporation; et al. ([Beverly Hills, CA] : Twentieth Century Fox Home Entertainment, 2016)
Told from Igor's perspective, we see the troubled young assistant's dark origins, his redemptive friendship with the young medical student Viktor Von Frankenstein, and become eyewitnesses to the emergence of how Frankenstein became the man, and the legend, we know today.
Title from container.
DVD release of the 2015 motion picture.
Special features: The making of Victor Frankenstein 7 part documentary ; galleries.
Music, Craig Armstrong ; editor, Charlie Phillips, Andrew Hulme ; director of photography, Fabian Wagner.
Daniel Radcliffe, James McAvoy, Jessica Brown Findlay, Andrew Scott, Freddie Fox, Charles Dance.
MPAA rating: PG-13; for macabre images, violence and sequence of destruction CHV rating: PG.
Keywords: Frankenstein, Victor (Fictitious character) -- Drama; Frankenstein's monster (Fictitious character) -- Drama; Human experimentation in medicine -- Drama; Scientists -- Drama; Monsters -- Drama; Feature films; Fiction films; Science fiction films; Thrillers (Motion pictures); Film adaptations; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Fiction films; Science fiction films; Thrillers (Motion pictures); Film adaptations